A randomized double-blinded study assessing the effect of different doses of transnasal dexmedetomidine on the median effective concentration of ropivacaine for a caudal block - Wang, Fu; Qu, Shijie; Chen, Yinglu; Liao, Bo; Ao, Li; Zhang, Hui; Zhou, Hongyan; Zhang, Liang (Frontiers in Medicine, 2024)
Perineural administration of dexmedetomidine (PN-DEX) can enhance the efficacy of local anesthetics administered in regional nerve block, meanwhile decrease the median effective concentration (EC50) of local anesthetics. Intranasal dexmedetomidine (IN-DEX) is more accessible for sedation during regional anesthesia because of non-invasive systemic administration, and also demonstrate synergism of local anesthetic. However, it remains unclear whether IN-DEX affect the EC50 of local anesthetics for the caudal block.This was a prospective single-center, double-blind, randomized controlled study.Patients scheduled to undergo elective hemorrhoidectomy were included and divided into three groups. 0.01ml/kg normal saline, 1μg/kg and 2μg/kg dexmedetomidine were dripped into both nostrils in Group IN-NS, IN-DEX1, and IN-DEX2 respectively at 15min before the caudal block.The initial concentration of ropivacaine was set at 0.4%, which was then varied by 0.025% using the up-and-down sequential allocation method. Vital signs, instances of hypotension and bradycardia with treatment and other adverse reactions were recorded and compared.The EC50 of ropivacaine was 0.275% (95% CI, 0.254%-0.296%) in group IN-NS, 0.257% (95% CI, 0.238%-0.276%) in group IN-DEX1 and 0.216% (95% CI, 0.195%-0.236%) in group IN-DEX2. The EC95 values of ropivacaine were 0.315% (95% CI, 0.295%-0.370%) in Group IN-NS, 0.297% (95% CI, 0.278%-0.351%) in group IN-DEX1 and 0.256% (95% CI, 0.236%-0.310%) in Group IN-DEX2. Compared with group IN-NS, EC50 of ropivacaine in IN-DEX2 was significantly decreased by 21.4% (P=0.001), while there was no significant difference between group IN-NS and IN-DEX1 (P=0.125). There were no differences in hypotension and bradycardia with treatment among the different groups.IN-DEX decreased the EC50 of ropivacaine for the caudal block, and there was a specific dose-dependent effect for IN-DEX. Side effects were similar among groups.